Secondary myoadenylate deaminase deficiency is not a common feature of inflammatory myopathies: A descriptive study - Wilkinson, Michael; Cash, Kathy; Gutschmidt, Bernice; Otto, Sophia; Limaye, Vidya (Frontiers in Medicine, 2022)
Background: Myoadenylate deaminase (MAD) deficiency is a form of metabolic myopathy, which generally causes only mild symptoms in the primary inherited form. Inflammatory myopathies are a group of autoimmune diseases which result in skeletal muscle weakness. In addition to inflammatory pathology, it has been speculated that non-inflammatory mechanisms, and possibly secondary MAD-deficiency, may potentially contribute to weakness in these conditions. Methods: We investigated for an association between these two myopathic processes through two complementary methods. Firstly, muscle biopsy records in South Australia over a 17-year period were retrospectively reviewed for diagnosis of myositis or MAD-deficiency, as well as associated clinical features. Secondly, a prospective arm histochemically tested all incident biopsy specimens over a 12-month period for MAD-deficiency. Results: In the retrospective arm, 30 MAD-deficient cases were identified (1.3% of all biopsies), with no significant difference observed in overall rates of myositis diagnosis between patients with intact and deficient myoadenylate deaminase activity (21.3% vs 26.7%, P=0.47). No cases of MAD-deficiency were detected in the prospective arm, despite 39 cases of myositis being identified over this period. Conclusions: Secondary myoadenylate deaminase deficiency is unlikely to be a major driver of symptoms in inflammatory myopathies.